797 ENDOTHELIAL FUNCTION AND RIGHT VENTRICLE DIMENSION AND FUNCTION IN PATIENTS WITH SYSTEMIC SCLEROSIS. (15th December 2022) - Croella, Francesca; Tricarico, Lucia; Alfieri, Simona; Altomare, Alberto; Mansueto, Natalia; Correale, Michele; Corrado, Addolorata; Pugliese, Rosanna; Romano, Matteo; Noviello, Giulia; Iacoviello, Massimo; Cantatore, Francesco Paolo; et al.
Abstract: Background: Systemic sclerosis (SSc) is a connective tissue disease characterized by the fibrosis of skin and internal organs, frequent immunity abnormalities and alterations in microvasculature. Among SSc complications, Pulmonary Hypertension (PH) is a frequent and severe one. Many echocardiographic parameters are used to assess pulmonary pressure and Right Ventricle (RV) dimension and function in these patients, from classical echocardiographic indexes to the most recent Speckle-Tracking Echocardiography (STE), while flow-mediated vasodilation (FMD) is the most common method to assess vascular reactivity. Aim of the study: To evaluate any possible relations between endothelial function and RV dimension and function in patients with SSc. Method: 48 sclerodermic patients underwent to echocardiographic examination and FMD, searching for relations between RV dimension and function and endothelial function indexes. For the RV we considered: 1) the eccentricity index (EI), 2) the fractional area change (FAC), 3) the ratio TAPSE/PAPs, 4) the RV basal diameter, 5) the RV free-wall strain and 6) the tricuspid regurgitation velocity; for the endothelium we evaluated the absolute difference between the radial artery diameters before and after 5 minutes of ischemia. We used a t-Student test (t-test) for unpaired samples with similar variances to verify the hypothesis that patients with altered RV parameters show a lower value in the absolute difference between radial diameters. Results: Only EI and endothelial function showed a significant relation. In fact, with a level of confidence of the 95% we can say that patients with an EI>=1, 1 report a minor increase in radial artery diameter than patients with EI<1, 1. Conclusions: In patients affected by SSc, the endothelial function is related to eccentricity index. Multicenter studies are needed in order to confirm the results of our study